Theoretical analysis of quantum noise suppression of light in bismuth-modified tellurite fibers - Sorokin, A. A.; Dorofeev, V. V.; Leuchs, Gerd (2022 International Conference Laser Optics, ICLO 2022 - Proceedingss, 2022)
Optical sources of squeezed quantum light are required for various ultraprecise measurements. For fiber-based Kerr squeezing technologies, silica fibers are widely used. Here an alternative fiber made of highly-nonlinear bismuth-modified tellurite glass is considered. We performed quantum dynamical simulations and analytical estimations and showed the possibility of attaining high quantum noise suppression up to-15 dB.
CRIS-Team Scopus Importer:2023-04-20
Keywords: bismuth-modified tellurite fiber; Kerr nonlinearity; quantum noise squeezing; Raman nonlinearity